The Effect of Arrival Vaccine Combination on Performance and Efficiency During the Receiving and Backgrounding Phase - Macie C. Weigand (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: Given the array of options for vaccination protocol combinations, the objective of this study was to evaluate a direct comparison of various product lines on their effects on feed intake early in the feeding period. Study Description: A total of 393 heifers were used in a 56-day backgrounding trial to assess the effects of three different arrival vaccine combinations on growth performance, feed efficiency, health, and water use during the receiving and back- grounding period. Treatments were: Pyramid [Pyramid 5 + Presponse SQ (Boehringer Ingelheim, Ridgefield, CT) and Bovilis Vision 7 Somnus with Spur (Merck Animal Health, Rahway, NJ)]; Stimulator [Stimulator 5 (Bimeda, Schaumburg, IL), Pro-Bac 4 (Bimeda, Schaumburg, IL), and Bovilis Vision 7 with Spur (Merck Animal Health, Rahway, NJ)]; and Bovi-Shield Gold [Bovi-Shield Gold One Shot (Zoetis Inc., Parsippany, NJ) and Bovilis Vision 7 Somnus with Spur]. The Bottom Line: These data suggest that the combination of vaccine treatments used upon arrival in this study had no negative effects on the growth performance, feed efficiency, or health outcome of heifers. It is important to consider the health status of the cattle being vaccinated as well as the number of injections given during a processing event.
Keywords: Combination vaccine; growth performance; newly receiving calves